ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PADA PENGENDARA SEPEDA MOTOR DI KABUPATEN INDRAMAYU - DEPI YULYANTI; Rudiansyah Rudiansyah; Fadjriyanto Fadjriyanto (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Accident cases in Indramayu Regency in 2019 there were 644 accident cases in Indramayu Regency, the accident cases were dominated by two-wheeled vehicles. The purpose of this study was to determine the effect of age, gender, education, SIM ownership and driving behavior with traffic accidents on motorcycle riders. The method in this study used an analytical research design with a cross sectional approach. Where the dependent variable in this study is a traffic accident and the independent variables are age, gender, education, driving license and driving behavior. The sampling technique used snowball with a population of 644 of the number of accident cases in 2019 and the sample in this study was 93 motorcycle riders in Indramayu Regency. Test the effect between the independent variable and the dependent variable using the Chi-Square Test and Multiple Logistics Regression. The results of this study indicate that there is no influence between age, gender, education, ownership and traffic accidents. There is an influence between driving behavior and traffic accidents. Of the five factors that have an influence on traffic accidents, namely driving behavior with a value of Exp(B) = 4.221, drivers who have poor driving behavior have a 4.22 times chance of traffic accidents. Conclusions in this study There is a relationship and influence of driving behavior with traffic accidents. For drivers who are not old enough and do not have a license.